Immunogenic Response of Brucella canisvirB10 and virB11 Mutants in a Murine Model - Palomares, Gabriela; Arellano, Beatriz; Hernandez, Rigoberto; Tenorio, Victor; Salas, Enrique; Suarez, Francisco; Diaz, Efrén (Frontiers in Cellular and Infection Microbiology, 2012)
The virB locus, which encodes the type IV secretion system, is a major component of virulence in Brucella. A non-polar virB10 mutant and a virB11 deletion mutant were constructed in Brucella canis. In the mouse model, both mutants were cleared at day 21 post-infection, indicating reduced virulence in mice. After challenging with wild-type B. canis, the amounts of CFU recovered at day 15 were significantly lower in the group previously vaccinated with the virB10 mutant. Levels of IgG1, IgG2a, IgG2b, and IgM, the induction of the cytokines IL-2, IL-4, IL-10, and the production of IFN-γ were measured in lymphocyte cultures. All strains elicited similar levels of different antibody isotype profiles, and no significant differences were detected (P < 0.05). The wild-type strain induced a rapid and strong INF-γ response at 24 h, while both mutants induced mild INF-γ responses at 24 h, which remained constant over the course of sampling. Our results suggest that the virB mutants elicit a protective immunity and may be considered as candidates for studies to be conducted in dogs against canine brucellosis.